IMPACT OF MATERNAL ANEMIA ON UMBILICAL CORD HEMOGLOBIN LEVEL – PROSPECTIVE OBSERVATIONAL CROSS-SECTIONAL STUDY. - Singh, Ritu; Samant, Meena; Nanda, Swaroop; Singh, Avinash Kumar (Student's Journal of Health Research Africa, 2024)
Introduction Anaemia is a prevalent condition in expecting mothers. Studies have shown that maternal anemia affects fetal growth and development which is evidenced by cord blood haemoglobin. The present study determines the effect of maternal anemia on fetal cord blood hemoglobin in the first and third trimesters. Method This study was conducted in a rural tertiary hospital in Eastern India in the department of obstetrics and gynecology. Women were recruited for 6 months and the follow-up analysis was conducted for up to 9 months. Women who delivered their babies at our institute were included in the study. Maternal hemoglobin in the first and third trimesters and cord blood hemoglobin after birth were measured to examine the impact of the former on the latter. Result Among 500 participants, the mean maternal hemoglobin was 11.51 ± 7.94 g/dl in the 1st trimester and 10.21 ± 1.52 g/dl in the 3rd trimester. Cord hemoglobin levels were 14.28 ± 2.08 g/dl. In the 3rd trimester, 342 (68.4%) women were anemic: 190 (55.56%) with mild, 137 (40%) with moderate, and 15 (4.3%) with severe anemia. Cord blood hemoglobin correlated positively with maternal hemoglobin in both trimesters (1st: F=5.55, p=0.001; 3rd: F=8.55, p=0.000). The 9-month follow-up showed that maternal anemia, especially in the 3rd trimester, was significantly associated with lower cord blood hemoglobin. Conclusion This study found a significant association between maternal hemoglobin and cord blood hemoglobin in the participants both in the 1st trimester and third trimester, and the association was identified to be linear. Recommendations Preventing neonatal complications requires early detection and treatment of anemia in pregnant women, especially in the third trimester. To protect maternal and fetal health, doctors should check hemoglobin levels throughout pregnancy.